Autopsy of a child with Spinal muscular atrophy Type I (Werdnig‑Hoffmann disease) - Manoj Gopal Madakshira; Sonal Singla; Kirti Gupta; Sayeeda Zahan; Pradip Paria; Jitendra Kumar Sahu (University of São Paulo, 2021)
Spinal muscular atrophy (SMA) is a heritable neuromuscular disorder which encompasses a large group of genetic disorders characterized by slowly progressive degeneration of lower motor neurons. The mutation is seen in the SMN1 gene mapped on chromosome 5. Depending on the age of the onset and the degree of severity, SMA has three subtypes. We discuss the autopsy findings in a case of Type 1 SMA also known by the name Werdnig-Hoffmann disease, to highlight the primary changes in the spinal cord, and skeletal muscle with association changes in the liver and terminal respiratory complications.